Molecular Characterization of Pasteurella multocida from Spontaneous Outbreaks in Cattle and Buffalo in Punjab - Filia, Gursimran; Kumar, Ashok; Mahajan, Vishal; Gupta, Tania; Vanisree, Yeleswarapu; Bal, Mandeep Singh; Randhawa, Charanjit Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Haemorrhagic septicemia (HS) is a peracute disease prevalent in India that is affecting cattle, buffalo and pigs. Microscopic and biochemical  analysis of isolated bacterial colonies is essential for reliable Pasteurella multocida detection in the laboratory along with the pathological  findings wherever possible. Present study involved a total of 247 animals from seven outbreaks, out of which 54 animals (21.86%) were  affected, with high mortality rate, i.e. 48.14% (26/54) in four districts (Ludhiana, Patiala, Moga and Jalandhar) of Punjab. Heart blood,  nasal and tracheal swabs collected and processed for bacterial isolation on the blood agar yielded grayish-white colonies of P. multocida,  which were confirmed microscopically and biochemically in accordance with their established protocols. Molecular characterization  was carried out using gene specific and type specific PCR. Histopathological studies on lungs, kidneys, liver and spleen collected from  the animals died due to the disease revealed the lesions of HS.
Keywords: Histopathology, Isolation, Pasteurella multocida Type B:2, PCR, Sequencing